Prevalence of Haemophilus Influenzae Biotypes and their Clinical Significance - H. Forouhesh Tehrani; A. Abdolahi; A. Asadi Asadabad; R. Mokarinejad; F. Nobahar; M. Oshaghi; M. Moradi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2007)
Background and objectives Haemophilus influenza can lead to several infections in humans. For example it can lead to meningitis, epiglottitis, pneumonia, cellulitis, bacteremia, septic arthritis and conjunctivitis. H. influenza can be classified into seven biotypes independent of their serotypes. Biotypes are determined by three tests including indol production, urease and ornithine decarboxylase. As specific biotypes are associated with different types of infections, sources and antimicrobial resistance patterns, this study was designed to evaluate biotyping in H.influenza and its relationship with the type of infection. Methods In an 18 month period from April 2005 to September 2006, all clinical specimens that were candidate for Haemophilus isolation, were cultured on standard chocolate agar and blood agar with staphylococcal streak technique. Those isolates that showed the phenomenon of satellitism were biotyped by indol production, urease and ornithine decarboxylation tests.Results From 24 samples positive for Haemophilus influenza, 11 were isolated from eyes, 11 from paranasal sinuses, one from cerebrospinal fluid (CSF) and one from blood. The isolates from sinuses belonged to the biotype III, the biotype of 6 of the eye isolates was II and that of the other 5 biotypes were III, and the isolates from blood were type I. Another biotype was not isolated from these samples.Conclusion In other studies, biotype I was the most frequently isolated biotype from CSF and blood. Biotypes II and III have been isolated from the eyes and sputum. The relationship between biotypes II and III in conjunctivitis is well documented. In this study, the most frequently isolated biotypes from conjunctivitis samples were II and III, type III was also common in sinusitis. Biotype IV has been isolated from genital tracts. Due to correlation of biotype and antimicrobial resistance, biotyping is recommended in Haemophilus isolates.Keywords: Influenza B Virus; Communicable Diseases; Infection